With empty arms, in the arms of pain: Gestational and neonatal loss (Research, Society and Development, 2020)
The aim of this study is to identify the woman's feelings and reactions to the gestational and neonatal mourning process. And to understand the woman's perception of her biological and marital role after the loss of her child. It is an integrative literature review, with a qualitative approach, carried out by searching for articles indexed in the Virtual Health Library (VHL), with the help of the following databases: Scientific Electronic Library Online (SCIELO), National Center for Biotechnology Information (PUBMED), Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database (BDENF), and Electronic Journals in Psychology (PEPSIC). The inclusion criteria include research between the years 2004 to 2020. As exclusion criteria, articles were not considered for monetary reward, incomplete and not converging with this study. To survey the data and composition of this study, 10 articles were analyzed. The results show the most frequent disturbing feelings of women facing the grieving process. Pregnancy represents the realization of a dream for the woman, a dream that becomes a nightmare when the pregnancy does not progress. We conclude that gestational or neonatal loss is one of the most complex and least validated mourners. We are saying that in a moment of life there is death. The incontinuity of life is wide open, no woman who becomes pregnant is psychologically prepared to suffer a loss, whatever the nature, constituting a period of crisis, generating great suffering and adaptive difficulties.